(untitled) (Ameghiniana, 2013)
Scapbonyx sanjuanensis sp. nov. is the rhynchosaur from the approximately Carnian aged Ischigualasto Formation of Western Argentina. The new species is slightly more advanced than Scapbonyx [iscberi from the Santa María Formation of Brazil, having a more specialized tooth structure and a more advanced tarsus. Re-study of the Brazilian rhynchosaurs shows that differences in relative size of the bones, used by van Huene to distinguish two genera, were more likely due to chemical pracesses of preservation, and the genus Cepbalonia is formally considered a junior synonym .of Scaphonyx. However, a wide range of skull variation exists in the Brazilian forms, but at present it does not appear to fall into groups that can be defined taxonornically. In broad terms, rhynchosaur evolution was fairly simple, and was apparently oriented towards increased specialization of the unique masticatory apparatus. General grouping of primitive, intermediate, and advanced forms are easily made, but differences between the Late Triassic advanced forms indica te that at least two, and possibly three, lineages arise from the Middle Triassic "íntermediate" rhynchosaurs.